2022
DOI: 10.3390/ijms23020683
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Natural Vascular Scaffold by Photochemical Treatment of the Extracellular Matrix for Vascular Applications

Abstract: The development of bioscaffolds for cardiovascular medical applications, such as peripheral artery disease (PAD), remains to be a challenge for tissue engineering. PAD is an increasingly common and serious cardiovascular illness characterized by progressive atherosclerotic stenosis, resulting in decreased blood perfusion to the lower extremities. Percutaneous transluminal angioplasty and stent placement are routinely performed on these patients with suboptimal outcomes. Natural Vascular Scaffolding (NVS) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…However, it is conceivable that the new covalent bonds introduce structural changes to the balloon-distended ECM, which drive these processes by modifying the integrin signaling in response to the hemodynamic changes following fistula surgery. Previous studies, using the photochemical treatment with the 10-8-10 Dimer, found altered structural appearance of ECM proteins and reduced ECM protein fragmentation, suggesting that the treatment provides lasting structural changes and resistance against matrix degrading enzymes [14].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, it is conceivable that the new covalent bonds introduce structural changes to the balloon-distended ECM, which drive these processes by modifying the integrin signaling in response to the hemodynamic changes following fistula surgery. Previous studies, using the photochemical treatment with the 10-8-10 Dimer, found altered structural appearance of ECM proteins and reduced ECM protein fragmentation, suggesting that the treatment provides lasting structural changes and resistance against matrix degrading enzymes [14].…”
Section: Discussionmentioning
confidence: 88%
“…ECM proteins, such as collagen fibers, elastin, and proteoglycans, are the major structural proteins of blood vessel walls. They convert mechanical stimuli generated by hemodynamic forces into biological signals via integrin-mediated mechanotransduction [14]. The integrity or reorganization…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is nothing “natural” in the concept, as the photosensitizer is a substance fully synthesized in laboratory, the radiation (wavelength 400–525 nm) is generated by manufactured instruments (xenon lamps or lasers), and luminal pre-dilation (which is crucial to the main application of the procedure) is achieved by standard balloon angioplasty. The procedure was initially intended to replace percutaneous transluminal angioplasty/stenting as a treatment for peripheral artery disease ( 106 ). It was claimed ( 105 ) that because only a limited number of crosslinks are produced in collagen, the resulting stent-like constructs will be not as rigid as the stents in current use.…”
Section: Introductionmentioning
confidence: 99%